Thalidomide in the treatment of multiple myeloma - Rokicka-Piotrowicz, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2001)
More than three decades after its withdrawal from the world market thalidomide is attracting growing interest because of its reported antiangiogenetic, immunomodulatory and anti-inflammatory properties. Recently, the drug was approved for sale in the United States for the treatment of erythrema nodosum leprosum. This review presents a new possibility of treatment of multiple myeloma patients with thalidomide. The dosage and side effects of thalidomide are described.